Can we evaluate the integral using Jordan lemma? $$ \int_{-\infty}^{\infty} {\sin ^2 (x) \over x^2 (x^2 + 1)}\:dx$$

What de we do if removeable singularity occurs at the path of integration?

  • $\begingroup$ Have you tried an approach like math.stackexchange.com/questions/34436/… ? $\endgroup$ – Siminore Aug 27 '12 at 10:59
  • $\begingroup$ thanks for hint!! I'll try and let you know!! $\endgroup$ – Monkey D. Luffy Aug 27 '12 at 11:00
  • $\begingroup$ @Siminore i didn't understand the concept of introducing $-2$ at the end Brain just stopped working :((((( $\endgroup$ – Monkey D. Luffy Aug 27 '12 at 11:25
  • $\begingroup$ It follows from $\sin^3 z = (\sin 3z - 3\sin z)/4$, in that case. $\endgroup$ – Siminore Aug 27 '12 at 11:41
  • 1
    $\begingroup$ @celtschk so how do I evaluate above integral? I am more interested in understanding How robjohn did on This Question math.stackexchange.com/questions/160022/… $\endgroup$ – Monkey D. Luffy Aug 27 '12 at 12:04

Using $\sin^2(z)=\frac12(1-\cos(2z))$, you should be able to handle this in much the same way as this answer.

Details (modified from the answer mentioned above)

Since $\lim\limits_{z\to0}\frac{1-\cos(2z)}{2z^2}=1$, the singularity of the integrand near $z=0$ is removable. Therefore, since the integrand vanishes for $z$ within $\frac12$ of the real axis as $|z|\to\infty$ and there are no singularities within $\frac12$ of the real axis, the integral does not change when shifting the path of integration from $z=t$ to $z=t-\frac{i}{2}$.

Now we can break up the integral as $$ \int_{-\infty-i/2}^{\infty-i/2}\frac{1-\cos(2z)}{2z^2(z^2+1)}\,\mathrm{d}z =\frac14\int_{\gamma^+}\frac{1-e^{2iz}}{z^2(z^2+1)}\mathrm{d}z +\frac14\int_{\gamma^-}\frac{1-e^{-2iz}}{z^2(z^2+1)}\mathrm{d}z\tag{1} $$ where $\gamma^+$ and $\gamma^-$ are as depicted below:

$\hspace{4.6cm}$path of integration

$\gamma^+$ circles two singularities ($z=0$ and $z=i$) clockwise, and $\gamma^-$ circles one singularity ($z=-i$) counter-clockwise.

All of the singularities are simple, so to get the residue at $z=z_0$, we just need to multiply by $z-z_0$ and taking $\displaystyle\lim_{z\to z_0}$

At $z=0$ the residue of $\displaystyle\frac{1-e^{2iz}}{z^2(z^2+1)}$ is $-2i$

At $z=i$ the residue of $\displaystyle\frac{1-e^{2iz}}{z^2(z^2+1)}$ is $\displaystyle\frac{1-e^{-2}}{-2i}$

At $z=-i$ the residue of $\displaystyle\frac{1-e^{-2iz}}{z^2(z^2+1)}$ is $\displaystyle\frac{1-e^{-2}}{2i}$

Putting these together with $(1)$ yields $$ \begin{align} \int_{-\infty}^\infty\frac{1-\cos(z)}{z^2(z^2+1)}\,\mathrm{d}z &=\frac{2\pi i}{4}\left(-2i+\frac{1-e^{-2}}{-2i}\right)-\frac{2\pi i}{4}\left(\frac{1-e^{-2}}{2i}\right)\\ &=\frac{\pi}{2}\left(2-\frac{1-e^{-2}}{2}-\frac{1-e^{-2}}{2}\right)\\ &=\frac\pi2+\frac{\pi}{2e^2}\tag{2} \end{align} $$

  • $\begingroup$ thanks man!! you are lifesaver!! $\endgroup$ – Monkey D. Luffy Aug 27 '12 at 22:58

Taking $$C_R:=[-R,-\epsilon]\cup\left(\gamma_\epsilon:=\{z=\epsilon e^{it}\;\;|\;\;0\leq t\leq \pi\}\right)\cup [\epsilon,R]\cup\left(\gamma_R:=\{z=Re^{it}\;\;|\;\;0\leq t\leq \pi\}\right)$$ $$f(z)=\frac{1-e^{2iz}}{z^2(z^2+1)}$$
we get $$\oint_{C_R}\frac{1-e^{2iz}\,dz}{z^2(z^2+1)}=2\pi i\,Res_{z=i}(f)=2\pi i\frac{1-e^{-2}}{i^2(2i)}=-\pi\left(1-e^{-2}\right)$$ But $$\oint_{C_R}f\,dz=\int_{-R}^{-\epsilon} f\,dx\,-\int_{\gamma_\epsilon}f\,dz+\int_\epsilon^Rf\,dx+\int_{\gamma_R}f\,dz$$ Using now the nice lemma in the answer here , we get $$\lim_{\epsilon\to 0}\int_{\gamma_\epsilon}f(z)dz=-i\pi\,Res_{z=0}(f)=-i\pi(-2i)=-2\pi$$ And either using Jordan's lemma or directly: $$\left|\int_{\gamma_R}f(z)\,dz\right|\leq \frac{1+e^{-2R\sin t}}{R^2(R^2-1)}\pi R\xrightarrow [R\to\infty]{}0$$ So passing to the limit when $\epsilon\to 0\,\,,\,\,R\to\infty\,$ and using Cauchy's Integral Theorem, we get: $$\int_{-\infty}^\infty \frac{2\sin^2x\,dx}{x^2(x^2+1)}=2\pi-\pi(1-e^{-2})=\pi\left(1+\frac{1}{e^2}\right)\Longrightarrow $$ $$\Longrightarrow\int_{-\infty}^\infty\frac{\sin^2 x\,dx}{x^2(x^2+1)}=\frac{\pi}{2}\left(1+\frac{1}{e^2}\right)$$


Hint, note that $ \cos(2x)=1-2\sin(x)^2 $, this suggest to consider the integral

$$ \int_{C} \frac{ {\rm e}^{2 i z} - 1 }{ z^2 (z^2 + 1)} dz \,.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.